Environmental impact of COVID-19 Vaccine waste: A perspective on potential role of natural and biodegradable materials. Issue 4 (August 2022) - Hasija, Vasudha; Patial, Shilpa; Kumar, Abhinandan; Singh, Pardeep; Ahamad, Tansir; Khan, Aftab Aslam Parwaz; Raizada, Pankaj; Hussain, Chaudhery Mustansar
Abstract: The mass immunization is the prioritised post-pandemic phase offering preventive countermeasure for COVID-19 pandemic. However, it is crucial to tackle the environmental impact of COVID-19 vaccine waste for sustainable vaccination management because a prolonged immunisation campaign is expected. As the pace of vaccine production, distribution and mass vaccination has been expedited, there is a simultaneous rise in plastic derived vaccine waste including syringes, needles, used/unused vaccine vials, vaccine packaging, and protective gear (surgical facemasks, gloves, face shields, etc). Henceforth, in view of the repercussions of heaping plastic waste in the environment, this article provides a perspective on the usage of synthetic and natural materials as potential substituents for vaccination tools. The biodegradable polymeric gums such as cellulose, gellan, pectin, etc. have been successfully applied for the fabrication of surgical facemasks. The highly suggestive practice is replacement of conventional polypropylene based plastics with bioplastics or paper for vaccine packaging. The usage of biodegradable bio-plastics as packaging material along with environmentally friendly face masks can help to achieve the zero waste approach. The discussion in the article significantly highlights the necessity of opting sustainable solutions of disinfecting and substituting vaccination tools for an environment friendly ongoing vaccination campaign. Graphical Abstract: ga1 Highlights: COVID-19 mass vaccination campaigns have reemphasized the use of plastics. Effects of discarded syringes, needles, discarded/used vaccine vials, single-use-plastics. Eco-friendly bio-based surgical face masks minimizes environment impact. Biodegradable alternatives made from bioplastics/natural polymers are sustainable solutions.